2010
DOI: 10.1007/s10549-010-1002-0
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a phase II study of nab-paclitaxel, bevacizumab, and gemcitabine as first-line therapy for patients with HER2-negative metastatic breast cancer

Abstract: In order to examine the efficacy and safety of nanoparticle albumin-bound paclitaxel (nab-P) in combination with bevacizumab (B) and gemcitabine (G) for the first-line treatment of patients with HER2-negative metastatic breast cancer (MBC). In this single-center, open-label phase II trial, patients with HER2-negative MBC received gemcitabine 1500 mg/m(2), nab-paclitaxel 150 mg/m(2), and bevacizumab 10 mg/kg (each administered intravenously) on days 1 and 15 of a 28-day cycle. The primary end point was progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 18 publications
1
45
0
2
Order By: Relevance
“…During the first-line treatment of HER2-negative BC, combinations of bevacizumab and nab-paclitaxel achieved responses of 30%-46% and PFS of 7.7-9.2 months [25,26]. Addition of gemcitabine to this combination showed responses of 76%, PFS of 10.4 months, and OS of 18 months [27]. With PFS of 6.6 months and OS of 17.8 months on EndoTAG™-1/paclitaxel combination therapy, similar results were obtained in the present study for a comparable subgroup (TNBC, ECOG 0/1, and first-line), presumably representing the most promising patient population for vascular-targeting agents such as EndoTAG™-1.…”
Section: Discussionmentioning
confidence: 98%
“…During the first-line treatment of HER2-negative BC, combinations of bevacizumab and nab-paclitaxel achieved responses of 30%-46% and PFS of 7.7-9.2 months [25,26]. Addition of gemcitabine to this combination showed responses of 76%, PFS of 10.4 months, and OS of 18 months [27]. With PFS of 6.6 months and OS of 17.8 months on EndoTAG™-1/paclitaxel combination therapy, similar results were obtained in the present study for a comparable subgroup (TNBC, ECOG 0/1, and first-line), presumably representing the most promising patient population for vascular-targeting agents such as EndoTAG™-1.…”
Section: Discussionmentioning
confidence: 98%
“…3. The available studies of nab-paclitaxel-containing regimens for metastatic TNBC demonstrate promising efficacy data, such as an ORR of 34-85% [Lobo et al 2010;Hamilton et al 2013;Rugo et al 2015], but future research is needed to answer questions as to the overall effectiveness and the ideal nab-paclitaxel regimen in this challenging setting. Subset analysis of randomized trials and recently reported realworld experiences also support the use of single-agent nab-paclitaxel for women with other disease features associated with poor prognostic factors, as visceral-dominant metastases and DFI of no less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one trial has been completed and published in which a TNBC-exclusive population was treated with nab-paclitaxel. [Lobo et al 2010]. Finally, a randomized phase III trial by the Cancer and Leukemia Group B (Trial CALGB 40502) compared qw paclitaxel 90 mg/m 2 given the first 3 of 4 weeks (qw3/4) plus bevacizumab 10 mg/kg every 2 weeks (q2w) versus nab-paclitaxel 150 mg/m 2 qw3/4 plus bevacizumab 10 mg/kg q2w or ixabepilone 16 mg/kg qw3/4 plus bevacizumab 10 mg/ kg q2w.…”
Section: Triple-negative Metastatic Breast Cancermentioning
confidence: 99%
“…22 Several trials adding other drugs to nab-paclitaxel have been conducted to further improve the efficacy, such as carboplatin, gemcitabine, bevacizumab, and herceptin. [23][24][25] On the basis of our knowledge, this is also the first trial showing that the already-strong antitumor activity of weekly nab-paclitaxel for MBC can be further increased by adding a chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 86%